PENGEMBANGAN MEDIA BOOKLET UNTUK MENINGKATKAN PENYESUAIAN DIRI SISWA KELAS VII SMP PGRI LEMBANG - Febrianty, sherly; Samsudin, Asep; Annisa, Dona Fitri (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2023)
To help students adjust to their new school, the author of the book "Development of a Media booklet to Improve Self-adjustment for Class VII Students of SMP PGRI Lembang" uses a Research and Development (R&D) approach to create a booklet designed to help students adapt. In addition, a customized questionnaire consisting of a total of 42 statement items was used in this investigation. Class VII students of SMP PGRI Lembang were the subjects of this study. Out of a total population of 27, only 8 were randomly selected to participate. In this study, we used descriptive percentages to analyze our data (including 27 participants). This study uses expert validation tests to determine whether or not the media to be tested for spaciousness is appropriate. This test involves media experts, materials, and practitioners. The results of the research on class VII A students before receiving guidance services for self-adjustment booklet media were very low with a percentage score of 43% which could be categorized as very low, and after students were given group guidance services with self-adjustment booklet media, the percentage score increased to 76%. The results of this research were carried out to increase students' understanding of the importance of self-adjustment so that students can get success both academically and non-academically.